Meeting special educational needs in primary classrooms inclusion and how to do it - Briggs, Sue 1953- (London Routledge, 2016)
There are greater numbers of children with Special Educational Needs and Disabilities (SEND) now attending mainstream schools. This fully updated and revised edition of Meeting Special Educational Needs in Primary Classrooms is written by an experienced teacher, adviser and SEN consultant and explains the challenges that these children face. This is a practical book full of guidance for teachers and teaching assistants who support children with SEND in mainstream primary classrooms.
1. Inclusion in the primary context -- 2. Working with families -- 3. Planning and teaching for inclusion -- 4. Support for inclusion -- 5. Assessment for inclusion -- 6. Want to play? Social interaction and behaviour -- 7. Communicating with children with learning difficulties -- 8. Transition: inclusion opportunities and challenges.
"A David Fulton book."--Cover.
Includes bibliographical references (pages 177-178) and index.
Keywords: Children with disabilities -- Education (Primary) -- Great Britain; Special education -- Great Britain